Distribution and elimination of protein therapeutics: A review - Sutradhar, Kumar Bishwajit; Khatun, Sabera; Al Mamun, Abdullah; Begum, Mamotaz (Stamford Journal of Pharmaceutical Sciences, 2012)
It was 1980s when the first therapeutic protein was launched in the market. It was recombinant DNAderived insulin. Since its inception, within the worldwide pharmaceutical sector, protein therapeutics has been enjoying the fastest growth, notably for the last few years. As a result it is assumed that the treatment methodology with the conventional drug therapy will be shifted towards therapeutic proteins in near future. It made revolution in the treatment of chronic diseases like cancer, diabetes, cardiovascular diseases. The major segments in protein therapeutics are monoclonal antibody, insulin, granulocyte-colony stimulating factor (G-CSF), coagulation factors etc. In this review paper we will discuss the general aspects of protein therapeutics with their advantages over small-molecule drugs, functional classification of therapeutic proteins and their uses. The pharmacokinetics of protein therapeutics, especially from the distribution and elimination characteristics of therapeutic proteins will be discussed in brief with relevant examples. The major challenges and future perspectives will also be presented in short. DOI: http://dx.doi.org/10.3329/sjps.v4i2.10433 S. J. Pharm. Sci. 4(2) 2011: 01-12